ICT for teaching assistants - Galloway, John.; Norton, Hilary (Abingdon, Oxon ; New York, NY : Routledge, 2011)
'The role of ICT in enhancing both teaching and learning in classrooms continues to develop, no more so than when in the hands of effective practitioners. This easy-to-use book outlines the many ways in which it can be used, both as a subject, and as a tool to support learning across the curriculum. Now fully updated to take into account innovations in ICT and the revised National Occupational Standards, ICT for Teaching Assistants looks at the impact of these changes and includes: Practical examples of how ICT, including web-based tools such as'blogs' and'wikis', can be used; Guidance to working competently and safely on the internet; Suggestions for activities with ideas for how these can be used in a variety of contexts; Advice on gathering evidence to help build assessment plans; Information on health and safety and legal requirements. With links throughout to the National Occupational Standards for Teaching Assistants at Levels 2 and 3, this accessible book is essential for teaching assistants who wish to develop their confidence in ICT'-- Provided by publisher.
Includes index.
Keywords: Education -- Great Britain -- Data processing; Information technology -- Great Britain; Teachers' assistants -- Great Britain